Optimization of specific multiplex DNA primers to detect variable CLU genomic lesions in patients with Alzheimer’s disease - Van Giau, Vo; An, Seong Soo A. (Biochip journal, 2015)
Recently, polymorphisms in the clusterin ( CLU ) or Apolipoprotein J (ApoJ) gene were reported to be involved in lipid metabolism, atherogenesis, and being associated with the risk of developing Alzheimer’s disease (AD). The influences from genetic variation has not been examined among Koreans. To screen genes with abnormal exon expression profiles, we developed PCR primer pairs for CLU gene. The new primer set can target specific regions of previously sequenced CLU gene. Primers were designed to target eight exon amplicons with flanking regions to optimize PCR amplification. One-hundred samples from clinically diagnosed Korean AD patients were selected for testing. We identified four single nucleotide polymorphisms (SNPs) in CLU through direct sequencing of the PCR products. These included three SNPs (rs7982, rs2279590 and rs3216167) that were previously reported variants in the SNP database (dbSNP), which could be found in NCBI. Interestingly, one new (NEW1) or extremely low-frequency mutation was found in more than one individual among the late-onset AD subjects. Our study suggests that CLU variants may also be an AD susceptibility factor among Koreans. Moreover, the findings of the study can be able to develop for simultaneous identify all of the genotypes of CLU mutation sites by DNA microarray PCR-based in the future.